New taxa of Plebejus eversmanni (Lang, 1884) and Polyommatus icarus (Rottemburg, 1775) (Lepidoptera, Lycaenidae) - Sergei V. Churkin; Pavel V. Bogdanov (Acta Biologica Sibirica, 2024)
The paper presents the descriptions of four new taxa: Plebejus eversmanni geminus ssp. nova from Tian-Shan (Suusamyr Mts.), P. eversmanni campulus ssp. nova from the East Pamirs, Polyommatus icarus lacuina ssp. nova (Mongolia, Mongolian Altai, Sutai Uul Mt.) and Polyommatus icarus incoronatus ssp. nova (Mongolia, Mongolian Altai, southern slopes, Mogoin-Gol r.).